Three-dimensional light scattering by a real liquid jet: VCRM simulation and experimental validation. (December 2019) - Duan, Qingwei; Han, Xiang'e; Idlahcen, Saïd; Fang Ren, Kuan
Highlights: An algorithm in the framework of VCRM is proposed to calculate the 3D light scattering by a large nonspherical particle with smooth surface. The ray tracing, calculation of divergence factor, phase shifts due to focal lines and optical path, cross polarization and the interpolation of bivariate data for the interference effect encountered in 3D scattering are addressed. The 3D scattered intensity by a real liquid jet with a varying cross section is calculated and interpreted based on the proposed method. Due to the curvature along the jet axis, the scattered light shows a very interesting pattern that the conventional calculation methods can hardly account for. Experiment has also been carried out to validate the proposed method. Abstract: This paper reports the first realization of an algorithm in the framework of the vectorial complex ray model (VCRM) to calculate the three-dimensional (3D) distribution of the scattered intensity by a large nonspherical particle with smooth surface. The ray tracing, divergence factor, phase shifts due to focal lines and optical path, and cross polarization are dealt with by an elegant way using vectorial rays and the wavefront curvature. A triangulation-based bivariate data interpolation is also developed for the superposition of the scattered complex amplitudes. As an example, the algorithm is applied to the prediction of the 3D scattering diagram by a real liquid jet which has a varying cross section. The simulated 3D scattering patterns are compared with experimental results. Good agreements are found not only on the spatial separation of different scattering orders but also on the intensities and the angular extension ranges.